Optimalization Characteristics of the Formulation Essential Oil Nanobiopesticide: Citrus hystrix, Melaleuca cajuputi, and Cymbopogon citratus from West Aceh, Indonesia - Sari, Putri Mustika; Lizmah, Sumeinika Fitria; Weihan, Rayhan Amadius (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
Research on essential oils as biopesticides is very much, so in the development of essential oils as biopesticides there are weaknesses, namely the nature of essential oils as the main ingredient is volatile, and environmental factors are easy to degrade. So it takes a formulation that can maintain the level of the main compound in the long term, and this can be achieved through nanoemulsion. Based on that, this study aims to optimalize the characteristics of the essential oil nanoemulsion formulation derived from Citrus hystrix (J-1), Melaleuca cajuputi (K-1), and Cymbopogon citratus (S-1) extracts so that it has properties worthy of being a biopesticide. So the method used is descriptive, by testing the stability of the formulation, transmittance, emulsion type, Particle Size Test, Polydispersity Index, and zeta potential. So the results of this study show that in the transmittance test J-1 (98.8%), K-1 (97.7%), S-1 (86.9%), pH test J-1 (5.94), K-1 (6.5), S-1 (6.68), viscosity test J-1 (4.63cPs), K-1 (4.34cPs), S-1 (4.39cPs), particle size test J-1 (10.9±0.05), K-1 (12.5±0.08), S-1 (12.6±0.15), polydispersity index test J-1 (0.563±0.04), K-1 (0.052±0.01), S-1 (0.635±0.08), zeta potential test J-1 (-18.9±1.51), K-1 (-19.9±1.41), S-1 (17.7±1.43). In the stability and emulsion type tests, the three formulation have the same characteristics, namely clear yellow color, distinctive odor, homogeneous, without sediment, without separation of 2 solution phases, and oil-in-water (o/w) emulsion type. Based on these data, it can be seen that the three formulation are stable and suitable to be biopesticides in further research.